2008
DOI: 10.1002/humu.20823
|View full text |Cite
|
Sign up to set email alerts
|

Variants of theMATP/SLC45A2gene are protective for melanoma in the French population

Abstract: In this study, we investigated whether variants in three key pigmentation genes-MC1R, MATP/SLC45A2, and OCA2--were involved in melanoma predisposition. A cohort comprising 1,019 melanoma patients (MelanCohort) and 1,466 Caucasian controls without skin cancers were studied. A total of 10 polymorphisms, including five functional MC1R alleles (p.Asp84Glu, p.Arg142His, p.Arg151Cys, p.Arg160Trp, and p.Asp294His), two nonsynonymous SLC45A2 variants (p.Phe374Leu and p.Glu272Lys), and three intronic OCA2 variants prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
43
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 68 publications
(69 reference statements)
7
43
0
Order By: Relevance
“…70 A recent French study exhibited similar findings, as the SLC45A2 variant, p.Phe374Leu, was again found to be significantly and strongly protective for CMM, with an OR of 0.32 (95% CI, 0.34-0.43). 71 Nan et al 65 found a different SLC45A2 variant, 1721 C[G, to be significantly associated with a reduction in risk for CMM, with an OR of 0.75 (95% CI, 0.60-0.95). A recent study found the SLC45A2 variant, 16891982, to be associated with a decreased CMM risk with an OR of 0.40.…”
Section: Mc1rmentioning
confidence: 96%
“…70 A recent French study exhibited similar findings, as the SLC45A2 variant, p.Phe374Leu, was again found to be significantly and strongly protective for CMM, with an OR of 0.32 (95% CI, 0.34-0.43). 71 Nan et al 65 found a different SLC45A2 variant, 1721 C[G, to be significantly associated with a reduction in risk for CMM, with an OR of 0.75 (95% CI, 0.60-0.95). A recent study found the SLC45A2 variant, 16891982, to be associated with a decreased CMM risk with an OR of 0.40.…”
Section: Mc1rmentioning
confidence: 96%
“…The ancestral variant 374 L of rs16891982 has been associated with olive and dark skin, and confers a protective effect against melanoma, even for individuals with a fair phenotype (ORs of 2.37–5.50) 59 61 62. This variant is more common in individuals from southern Europe and the Mediterranean region, and there is a decreasing gradient of allele frequency from the south to the north of Europe 60 63…”
Section: Medium Penetrance Genesmentioning
confidence: 99%
“…The two SNPs most significantly associated with melanoma risk are rs1129038 and rs12913832, the latter being a key determinant of human blue-brown eye colour 67 68 . PLA2G6 is associated with pigmentation and naevi, while CASP8 , TERT , AGR3 , MTAP/CDKN2A and FTO are associated with variation in naevus density 14 61 63 65–67 69–78. In addition to its role in naevus count, TERT is also associated with telomere length, as is OBFC1 73.…”
Section: Low Penetrance Genesmentioning
confidence: 99%
“…In this area, the most frequently implicated genes are those involved in the pigmentation pathway [6,7]. The best studied gene is the melanocortin 1 receptor (MC1R) [8], but variants in other pigmentation genes have recently been shown to modulate the risk of SK, such as those coding for the membraneassociated transporter protein (SLC45A2/MATP) [6,[9][10][11], the agouti signaling protein (ASIP), the tyrosinase enzyme (TYR), the tyrosinase-related protein 1 (TYRP1) [12], the OCA2 protein [13], and the endothelin receptor B (EDNRB) [14]. Besides pigmentation genes, common variants on 1p36, 1q42, keratin 5 (KRT5) gene, 7q32 and 9p21 have been shown to be associated with BCC susceptibility but not with CM or pigmentation traits [11].…”
Section: Introductionmentioning
confidence: 99%